Improving Science Process Skills through the Discovery Learning model - Azis, Sri Rofida; Fatmawati, Baiq; Asri, Indra Himayatul (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2024)
This study examines the effectiveness of implementing the Discovery Learning model on students' science process skills. The research method used is a quasi-experiment with a Pretest-Posttest Control Group Design, involving two groups: an experimental class (n = 16) using Discovery Learning and a control class (n = 15) using the lecture method. The research instruments include achievement tests, observation sheets, and interviews with teachers and students. The results indicate that students who learned through Discovery Learning experienced a significant improvement in science process skills, particularly in observing, classifying, predicting, and communicating learning outcomes. Statistical analysis using the t-test showed a significant difference between the experimental and control groups, with tcalculated=3.17 = 3.17 greater than ttable=2.045 at a significance level of p<0.0. These findings highlight the importance of inquiry-based learning strategies in improving the quality of science education. The study was conducted over eight weeks, allowing for a comprehensive assessment of student progress.